Optimized husbandry and targeted gene-editing for the cnidarian Nematostella vectensis - Carvalho, João E.; Burtin, Maxence; Detournay, Olivier; Amiel, Aldine R.; Röttinger, Eric (bioRxiv, 2024)
Optimized laboratory conditions for research models are crucial for the success of scientific projects. This includes the control of the entire life cycle, access to all developmental stages and maintaining stable physiological conditions. Reducing the life cycle of a research model can also enhance the access to biological material and speed up genetic tool development. Thus, we optimized the rearing conditions for the sea anemone Nematostella vectensis, a cnidarian research model to study embryonic and post-metamorphic processes, such as regeneration. We adopted a semi-automated aquaculture system for N. vectensis and developed a dietary protocol optimized for the different life stages. Thereby, we increased spawning efficiencies and post-spawning survival rates, and considerably reduced the overall life cycle down to two months. To further improve the obtention of CRISPR-Cas9 mutants, we optimized the design of sgRNAs leading to full KO animals in F0 polyps using a single sgRNA. Finally, we show that NHEJ-mediated transgene insertion is possible in N. vectensis. In sum our study provides additional resources for the scientific community that uses or will use N. vectensis as a research model. Optimized life cycle, in combination with efficient gene-editing approaches facilitates the establishment of genetic tools in N. vectensis, an emerging model for environmental stress response, regeneration, and longevity.